(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of Azospirillum and vermicompost through application of different treatment combinations on eight years old bearing grafted plants of custard apple cv. Raydurg during 2018-2019. The results revealed that T10 (AZS @ 50 g + V.C. @ 10 kg/plant) was found optimally better in improvement of morphometric attributes. The application of (AZS @ 50 g + V.C. @ 10 kg/plant) in T10 treatment resulted in better crop at low inputs-use efficiency without having adverse effect on environment and offers an alternative for organic cultivation involving bioinnoculants. The studies harness the role of organic inputs along with AZS in optimization of fruit yield and maintenance of soil health parameters for efficient utilization of natural resources.